Comparison of Neutrophile-to-Lymphocyte Ratio Between Dengue Haemorrhagic Fever and Dengue Shock Syndrome in Pediatric Patients at Anutapura Hospital - Amri, Imtihanah; Rahma, Rahma; Hutasoit, Gina Andyka; Putri, Ayu Sekarani Damana; Harun, Haerani; Rasyid, Riyadh (Media Publikasi Cendekia Indonesia, 2025)
Dengue Hemorrhagic Fever (DHF) is an acute viral infectious disease that attacks the body. DHF is divided into 4 grades (I, II, III, IV), in which degrees 3 and 4 are also known as Dengue Shock Syndrome (DSS). When the disease severity is detected too late, it can be fatal. Therefore, a predictor or inflammatory marker is needed to detect and predict this. In this study, the inflammatory marker assessed is the NLR value. This study compares the neutrophil-lymphocyte ratio and the incidence of Dengue Hemorrhagic Fever and Dengue Shock Syndrome in pediatric patients at the Anutapura Regional Hospital, Central Sulawesi Province. This study uses an observational analytical method with a cross-sectional design using secondary data from medical records at the Anutapura Regional Hospital, Palu, in 2021-2023. The sample included is patients with a diagnosis of DHF, totaling 100 samples. The sampling technique used is random sampling. Based on the Mann-Whitney test, a significant difference (p = 0.001) was found in the NLR value between DHF and DSS. The mean NLR in DHF was lower (1.28 (±0.98 SD)) than in DSS (2.07 (±1.59 SD)). There was no significant relationship between age (p=0.217) and gender (p=0.597) in the DHF and DSS groups. It is then concluded that there is a significant difference in NLR values between DHF and DSS, where NLR values are lower in DHF and higher in DSS.